Pengaruh Pembinaan Kerohanian terhadap Kemampuan Anger Management Warga Binaan - Febi Fauziah (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
This paper aims to know the implementation of spiritual guidance in Correctinal Facility, looking for the presence or absence of influence between spiritual guidance with the ability of anger management of the jailbird, and measure the condition of anger management of the jailbird in Correctional Facility. The research method used descriptive method involving data source from the jailbird and the officer responsible for the activity of spiritual guidance. Data analysis with quantitative analysis. The results showed spiritual guidance conducted on Monday-Friday consisting of tausiah, Iqro, Juz 'Amma and Al-Qur'an and pesantren shalihah. There is influence between spiritual guidance and anger management and the anger management of the jailbirds people who follow the spiritual guidance is categorized as good. Tulisan ini bertujuan untuk mengetahui pelaksanaan pembinaan kerohanian di Lapas, mencari ada tidaknya pengaruh antara pembinaan kerohanian dengan kemampuan anger management warga binaan, dan mengukur kondisi anger management warga binaan di Lapas Wanita Kelas II A Bandung. Metode penelitian menggunakan metode deskriptif yang melibatkan sumber data dari warga binaan sekaligus petugas yang bertanggung jawab atas kegiatan pembinaan kerohanian. Analisis data dengan analisis kuantitatif. Hasil penelitian menunjukan pembinaan kerohanian dilaksanakan pada hari senin-jum’at yang terdiri dari tausiah, Iqro, Juz ‘Amma dan Al-Qur’an serta pesantren shalihah. Terdapat pengaruh antara pembinaan kerohanian dan anger management. Serta kondisi anger management warga binaan yang mengikuti pembinaan kerohanian tergolong kategori baik.